Topologically protected optical pulling force on synthetic particles through photonic nanojet; Nanophotonics; Vol. 13, iss. 2 - Ren Yu-Xuan; Frueh J. C. Johannes Christoph; Zhang Zisheng; Rutkowski S. Sven; Zhou Yi; Mao Huade; Kong Cihang; Tverdokhlebov S. I. Sergei Ivanovich; Liu Wen; Wong Kenneth K. Y.; Li Bo (2024, 2024)
Title screen